Computational modeling of high performance cementitious thin shell elements under in-plane shear. Issue 2 (25th January 2018) - Koukouselis, Apostolos; Mistakidis, Euripidis
ABSTRACT: High-performance cementitious materials are widely used in the construction of thin shell elements. This study investigates a simulation method based on composite layered shells for the nonlinear analysis of high-performance cementitious elements under in-plane shear. A tube torsion test is simulated and analyzed with MSC-MARC and its results are compared to an alternative calculation method, the Simplified Model for Combined Stress resultants (SMCS), as well as with experimental data. The simulation method is found to produce accurate results for fully under-reinforced elements with a range of strong to weak reinforcement ratios less than 2.